PSYCHOLOGICAL CAPITAL DAN WORK ENGAGEMENT: KONTRIBUSI HOPE, OPTIMISM, RESILIENCE DAN EFFICACY TERHADAP WORK ENGAGEMENT - Mardiah Mardiah; Zaki Nur Fahmawati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Recently, market demand in the coal mining industry has increased, so companies need to pay attention to HR productivity as one of the important factors to meet market targets. Company "X" in Kalimantan is one of the coal mining subcontractors that must meet the targets set by the client company. To meet the target, the company needs to know the work engagement that exists in HR. Work engagement has an important role in HR productivity and this work engagement is influenced by psychological capital. The purpose and benefit of this study is to determine the contribution of psychological capital to work engagement in HR in a coal mining subcontracting company. This research method is relational quantitative. Data analysis uses multiple correlations and simple regression. The result of this study is that psychological capital has an influence of 15.4% on work engagement. This means that the influence of psychological capital on work engagement is low and there are still various other variables that influence and are not the focus of this study.